2015
DOI: 10.2340/16501977-1998
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of cognition to health-related quality of life in good-outcome survivors of out-of-hospital cardiac arrest

Abstract: The cognitive impairments frequently reported in OHCA survivors with good outcomes may compromise health-related quality of life. Cognitive functioning should be addressed even in survivors with rapid recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 32 publications
(75 reference statements)
2
25
1
7
Order By: Relevance
“…3,4 However, residual cognitive impairments are common among these survivors. [5][6][7][8][9][10][11][12][13] Cognitive impairments are associated with a reduction in both health-related quality of life and participation in society. 10,11,14 Memory, attention, and executive functions, as well as fine-motor coordination are most frequently impaired.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 However, residual cognitive impairments are common among these survivors. [5][6][7][8][9][10][11][12][13] Cognitive impairments are associated with a reduction in both health-related quality of life and participation in society. 10,11,14 Memory, attention, and executive functions, as well as fine-motor coordination are most frequently impaired.…”
Section: Introductionmentioning
confidence: 99%
“…Most impairments are mild or moderate. [3][4][5][6][7][8][9][10][11] An increased duration of coma after initial resuscitation 5,6,11,14,15 and an increased duration of time to return of spontaneous circulation (ROSC) 16 have each been correlated with a reduced cognitive outcome; however, other studies do not support these conclusions. 6,13,17 Few previous studies have addressed cognitive outcomes in combination with structural cerebral magnetic resonance imaging (MRI) analytic methods in long-term survivors of cardiac arrest.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to a greater susceptibility to changes in cognitive functionality with decreased kidney function. Understanding cognitive dysfunction is critical, as it impacts overall functioning and quality of life in both mental (Fujino et al, 2016;Tan, Thomas, & Rossell, 2014) and physical disorders (Orbo et al, 2015;Schuurs & Green, 2013), and specifically CKD (Seidel et al, 2014;Weiner & Seliger, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…7 Both cognitive impairment and emotional problems may affect patients' ability to return to activities in everyday life 1,3,8 and are important determinants of healthrelated quality of life (HRQoL). [9][10][11] Health-related quality of life in CA-survivors is mostly reported to be good and comparable to normative data, but subgroups of survivors have a worse outcome, 11,12 and more than half (56%) of out-of-hospital cardiac arrest (OHCA) survivors in a large Australian study rated their HRQoL to be lower than prearrest. 12 In more descriptive analyses of HRQoL, some areas like vitality 13 and social participation 10,14 were lower for CA-survivors compared with the general population, and in another trial, 74% of OHCA-survivors reported decreased societal participation 1 to 6 years postarrest.…”
mentioning
confidence: 86%